Low cost softswitch using SIP protocol - Abdul Rahman, Abdul Wahab; Erdogan, Sevki Serkan (2009)
Softswitch is a solution to many modern day Internet telephone networks and switching for routing problems. Softswitch can handle many types of calls, such as PC-to-PC, PC-to-phone, SMS, MMS and many others. Besides, it can deploy different types of applications and services for each call connection. The types of calls supported depend on the design and scope of the softswitch framework. In this paper, a low cost softswitch solution is proposed and developed based on the Session Initiation Protocol (SIP). PC-to-PC calls are examined and text to speech conversion is employed to test the softswitch.